Unique Adsorption Properties of Cationic Dyes Malachite Green and Rhodamine-B on Longan (Dimocarpus longan) Peel - Risfidian Mohadi; Normah; Erni Salasia Fitri; Neza Rahayu Palapa (Science and Technology Indonesia, 2022)
This research converts agricultural waste Longan (Dimocarpus longan) Peel is used in the adsorption process to reduce cationic dyes rhodamine-B and malachite green contaminants from aqueous solution. Longan (Dimocarpus longan) Peel was characterized by FT-IR, analysis XRD, SEM, BET, and TG-DTA. The characterization results show that Longan (Dimocarpus longan) Peel contains cellulose compounds and has a specific surface area 17.175 m2/g, with this Longan (Dimocarpus longan) Peel has the potential as a bio adsorbent. The adsorption capacity is proven by adsorption capacity (Qm) shows that the bioadsorbent adsorption of malachite green has a large adsorption capacity of 182.64 mg/g, while the adsorption capacity of rhodamine-B (Qm) reaches 52.557 mg/g and this bioadsorbent longan (Dimocarpus longan) peel is effective the adsorption was stable until the third cycle.